Creative Economy in Development of Micro , Small and Medium Enterprises : A Case Study in Tangkelek , Padang City - Rizky Aulya, Vivi; Okta Safira, Adhe; Evanita, Susi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Study This aim For analyze role economy creative in development of Tangkelek MSMEs in Padang City based on wisdom Minangkabau local . The method used is study descriptive qualitative through studies library with utilizing secondary data from literature and documents related. Research results show that implementation economy creative in Tangkelek MSMEs reflected through innovation design product , differentiation based culture local , as well as utilization digital technology in Marketing . Creative economy play a role in increase mark add, power competitiveness and sustainability business although with capital limitations . Research This conclude that economy creative own role strategic in support development of local MSMEs and the need supported by the increase quality source Power man as well as policy sustainable government .​